PENERAPAN TEKNOLOGI INFORMASI DALAM MENINGKATKAN EFISIENSI KERJA PETANI DI DESA LAINUNGAN, KECAMATAN WATTANG PULU, KELURAHAN LAWAWOI - Baharuddin Baharuddin (Jurnal Pengabdian Masyarakat, 2024)
The use of information technology among farmers in Lainungan Village is still limited, which hinders work efficiency and agricultural productivity. This Community Service (PkM) activity aims to improve farmers' understanding of information technology through training in the use of applications for crop management, irrigation management, and online marketing. The method used is practical training with pre-test and post-test to measure the increase in understanding. The results of the training showed a significant increase in understanding of information technology, with an average score increasing by 45%. Several farmers have succeeded in implementing applications for recording harvest results, irrigation management, and online product marketing, which have the potential to increase their work efficiency and market access.